2013
DOI: 10.1002/anie.201304765
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Study of the Gas‐Phase Electrolysis of Water on Platinum by NAP‐XPS

Abstract: Chasing down the active state: Near-ambient-pressure X-ray photoelectron spectroscopy was used to study the surface of a Pt electrode during the oxygen evolution reaction (OER). A hydrated Pt metal phase with dissolved oxygen in the near-surface region is OER-active and considered to be the precursor of the analytically detected PtO2 , which is in fact the deactivation product of the electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
156
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(172 citation statements)
references
References 32 publications
(38 reference statements)
7
156
0
9
Order By: Relevance
“…The surface undergoes a clear reconstruction upon OER conditions transitioning from a at metallic surface at OCP and low applied potentials (as conrmed by the low surface roughness (SR) values) to a high surface area oxidic system aer catalytic conditions, characterized by a much higher SR then the pristine surface. Therefore, we believe that the so-called "gelly structure" reported in literature for Pt surfaces under OER conditions in acidic electrolytes, 27,43,44 also occurs when the reaction is driven in alkaline environments. Using the previously described simulations, we can investigate the chemistry of the mesoporous ("gelly") structure, which is composed of a Pt Fig.…”
Section: Evolution Of Pt Surface Chemistry As a Function Of The Applimentioning
confidence: 99%
See 2 more Smart Citations
“…The surface undergoes a clear reconstruction upon OER conditions transitioning from a at metallic surface at OCP and low applied potentials (as conrmed by the low surface roughness (SR) values) to a high surface area oxidic system aer catalytic conditions, characterized by a much higher SR then the pristine surface. Therefore, we believe that the so-called "gelly structure" reported in literature for Pt surfaces under OER conditions in acidic electrolytes, 27,43,44 also occurs when the reaction is driven in alkaline environments. Using the previously described simulations, we can investigate the chemistry of the mesoporous ("gelly") structure, which is composed of a Pt Fig.…”
Section: Evolution Of Pt Surface Chemistry As a Function Of The Applimentioning
confidence: 99%
“…Moving towards realistic operating conditions, Arrigo et al recently studied Pt nanoparticles deposited on an acidic-polymer membrane using ambient pressure X-ray photoelectron spectroscopy (APXPS) in a humidied (solid/gas interface) environment. 27 The authors found that the rst stage of Pt oxidation involves the formation of a surface Pt oxide 27,33 where atomic oxygen (O) is weakly bound to Pt (Pt-O).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theory has studied the reaction [73,83] in detail. Experiments reveal that the working electrode is of complex chemical composition [84,85] with still unknown assignments of function of the various components. Advanced nanotechnology [86][87][88] tries to minimize the use of precious metals in the functional materials but is confronted with even larger challenges of stability of the system.…”
Section: The Chemical Toolbox Of Cecmentioning
confidence: 99%
“…The challenges are the same if this is done directly by photoelectro-catalysis or by electrolysis. Not issues of technical optimization but fundamental challenges in the understanding of the elementary steps during water splitting [25] are here the challenges.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%